Effect of Test Dimensionality and Strength of their Relationship on Statistical Properties and Standard Errors of Person Fit Indices - Rashid Al-mehrzi; Yousef Abu Shindi (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
The study aims to examine the effect of test dimensionality and the strength of their relationship on statistical properties and standard errors of three-person fit indices (Wright, Drasgow, Almehrizi) using seven simulated data sets of 1000 subjects. These data sets result from two factors: Number of dimensions (three levels: one, two, three) and relationship strength among dimensions (three levels: 0.0, 0.4,.8). Results revealed that Drasgow and Almehrizi indices showed the highest percentages of aberrant responses which were close to expected rates (5%) whereas Wright index showed the lowest. Descriptive statistics showed that the Almehrizi index was the closest to the descriptive statistics of standard normal distribution. Also, the result showed that test dimensionality and strength of interrelationship among dimensions affected the standard errors of both the mean and variance of the Wright index, whereas did not affect the standard errors of both the mean and variance of the Almehrizi index and Drasgow index. Almehrizi index was the most consistent index, especially with variance.